Clinical and molecular spectrum of CHOPS syndrome. Issue 7 (6th May 2019) - Raible, Sarah E.; Mehta, Devanshi; Bettale, Chiara; Fiordaliso, Sarah; Kaur, Maninder; Medne, Livija; Rio, Marlene; Haan, Eric; White, Susan M.; Cusmano‐Ozog, Kristina; Nishi, Eriko; Guo, Yiran; et al.
Abstract: CHOPS syndrome is a multisystem disorder caused by missense mutations in AFF4 . Previously, we reported three individuals whose primary phenotype included cognitive impairment and coarse facies, heart defects, obesity, pulmonary involvement, and short stature. This syndrome overlaps phenotypically with Cornelia de Lange syndrome, but presents distinct differences including facial features, pulmonary involvement, and obesity. Here, we provide clinical descriptions of an additional eight individuals with CHOPS syndrome, as well as neurocognitive analysis of three individuals. All 11 individuals presented with features reminiscent of Cornelia de Lange syndrome such as synophrys, upturned nasal tip, arched eyebrows, and long eyelashes. All 11 individuals had short stature and obesity. Congenital heart disease and pulmonary involvement were common, and those were seen in about 70% of individuals with CHOPS syndrome. Skeletal abnormalities are also common, and those include abnormal shape of vertebral bodies, hypoplastic long bones, and low bone mineral density. Our observation indicates that obesity, pulmonary involvement, skeletal findings are the most notable features distinguishing CHOPS syndrome from Cornelia de Lange syndrome. In fact, two out of eight of our newly identified patients were found to have AFF4 mutations by targeted AFF4 mutational analysis rather than exome sequencing. These phenotypic findings establish CHOPS syndrome as a distinct, clinically recognizable disorder. Additionally, we report three novel missense mutations causative for CHOPS syndrome that lie within the highly conserved, 14 amino acid sequence of the ALF homology domain of the AFF4 gene, emphasizing the critical functional role of this region in human development.